Assessment of reliability parameters of in-plant power supply schemes with two-transformer substations - Petrova R. M.; Gracheva E. I. (Vestnik MGTU)
In the process of designing in-plant power supply systems, it is necessary to determine their rational redundancy. The reliability of the power supply system has been established for the following variants of the circuit of two-transformer 10/0.4 kV substations: without redundancy; with redundancy (when installing a sectional switch); with double redundancy (when installing a sectional switch and a backup jumper for 0.4 kV). The calculation data have shown that the reliability of the circuit without redundancy is 1.87 times lower compared to the circuit with redundancy and 3.17 times lower than with the circuit with double redundancy. Graphic dependencies of the mean time between failures of power supply circuits with two-transformer substations from different rated capacities of shop transformers have been obtained for three variants: without redundancy; with redundancy; with double redundancy. The optimal condition is to use a smaller number of transformer substations (respectively, transformers) while maintaining the load factor of 0.8. When comparing the graphs, it has been found that the longest mean time between failures is achieved with double redundancy, and the shortest – with no redundancy. The research results can be recommended for use in the process of designing in-plant power supply systems to assess and improve the reliability and efficiency of equipment operation.